PENDIDIKAN ISLAM PERSPEKTIF IKHWANUS SHAFA DAN RELEVANSINYA DENGAN PENDIDIKAN ISLAM KONTEMPORER - Huswatul Hasanah (Universitas Islam Madura, 2023)
Education is one of the paths that humans must take to become happy. A person can improve their quality in the form of physical and mental abilities through the educational process. Ikhwanus Shafa, is a group of Islamic thinkers who study and offer concepts of Islamic education; which includes religious-rational understanding. This article aims to find out about the educational perspective of the Ikhwanus Shafa and its relevance to contemporary Islamic education. The research method in this writing is library research which is qualitative in nature. The primary data source for this writing is a book by Maragustam entitled